2018
DOI: 10.1111/bcpt.13175
|View full text |Cite
|
Sign up to set email alerts
|

Chronic administration of theobromine inhibits mTOR signal in rats

Abstract: Theobromine is a caffeine derivative and the primary methylxanthine in Theobroma cacao. We have shown previously that theobromine inhibits the Akt-mammalian target of rapamycin (mTOR) signal in vitro. In this study, we investigated whether orally administered theobromine could inhibit mTOR activity in rats. mTOR is phosphorylated by Akt. Thus, the level of phosphorylated mTOR was used as an index of mTOR activity. Male Wistar rats were divided into two groups. The control group (CN) was fed a normal diet, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…In our previous study, we confirmed that mice fed TB performed better on learning tasks and TB acted as a phosphodiesterase (PDE) inhibitor [9,10], by enhancing the cAMP/cAMP-response element-binding protein (CREB)/brain-derived neurotrophic factor (BDNF) pathway [7]. We also confirmed that TB supplemented chow-inhibited mTOR signaling in the brain and liver [11]. In the current experiment, we want to assess the effects of TB on rats, using a prolonged feeding period of 73 days, and to check whether different types of memory functions are affected by a variety of behavior experiments.…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations
“…In our previous study, we confirmed that mice fed TB performed better on learning tasks and TB acted as a phosphodiesterase (PDE) inhibitor [9,10], by enhancing the cAMP/cAMP-response element-binding protein (CREB)/brain-derived neurotrophic factor (BDNF) pathway [7]. We also confirmed that TB supplemented chow-inhibited mTOR signaling in the brain and liver [11]. In the current experiment, we want to assess the effects of TB on rats, using a prolonged feeding period of 73 days, and to check whether different types of memory functions are affected by a variety of behavior experiments.…”
Section: Introductionmentioning
confidence: 55%
“…To exert material effects against cognitive disorders, TB must be taken up in the brain from the blood by crossing over the BBB. Our previous data showed that TB was detectable in rat plasma and the brain after 30 and 40 days of TB ingestion, and gradually increased in a time-dependent manner [11]. The concentration of TB in rat brain and plasma after 40 days of TB ingestion might have been sufficient to produce significant pharmacological effects, as described in [4,7,47].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Theobromine is the primary methylxanthine found in products made from cacao (Theobroma cacao) [12]. We previously reported that theobromine acts as a phosphodiesterase inhibitor that increases intracellular cyclic adenosine monophosphate (cAMP) [13,14] levels and permeates through the blood–brain barrier [14,15]. Furthermore, cAMP signaling essentially influences the brain mechanism that mediates neural wiring and cognitive processes [16,17,18].…”
Section: Introductionmentioning
confidence: 99%